The Relationship Between Social Media and Stress Levels of Adolescents in Indonesia - Sofyan, Iradat Rayhan (Sinergi International Journal of Psychology, 2023)
This qualitative study looks into the connection between Indonesian teenage stress levels and social media use. During semi-structured interviews with Indonesian teenagers between the ages of 13 and 18, several themes surfaced that demonstrated the complex relationship between social media and teenage wellbeing. Social media platforms facilitate social contact, but they also include stresses like social comparison, FOMO, and cyberbullying, as reported by participants. Social media is a source of both connection and stress. Teenagers use a variety of coping mechanisms, such as placing limits on their use of social media, going offline, practicing mindfulness, and asking for social support. Addressing social media-induced stress in Indonesian teenagers requires culturally sensitive methods that take into account local norms and beliefs. The results highlight the significance of encouraging digital literacy, creating safe spaces, and giving teenagers the tools they need to use social media appropriately. Policies and interventions to encourage positive mental health outcomes in the digital era can be devised by comprehending the complexity of social media's impact on teenage well-being.